Probing Local Electrostatics of Glycine in Aqueous Solution by THz Spectroscopy. Issue 7 (21st December 2020) - Sebastiani, Federico; Ma, Chun Yu; Funke, Sarah; Bäumer, Alexander; Decka, Dominique; Hoberg, Claudius; Esser, Alexander; Forbert, Harald; Schwaab, Gerhard; Marx, Dominik; Havenith, Martina
Abstract: Based upon precise terahertz (THz) measurements of the solvated amino acid glycine and accompanying ab‐initio molecular‐dynamics simulations, we show that the N‐C‐C‐O open/close mode at 315 cm −1 serves as a sensitive, label‐free probe for the local protonation of the amide group. Experimentally, we can show that this holds not only for glycine but also for diglycine and valine. The approach is more general, since the changes due to protonation result in intensity changes which can be probed by THz time domain (0–50 cm −1 ) as well as by precise THz‐FT spectroscopy (50–400 cm −1 ). A detailed analysis allows us to directly correlate the titration spectra with p K a values. This demonstrates the potential of THz spectroscopy to probe the charge state of a natural amino acid in water in a label‐free manner. Abstract : Based upon precise terahertz (THz) measurements of the solvated amino acid glycine and accompanying ab‐initio molecular‐dynamics simulations, it is shown that the N‐C‐C‐O open/close mode at 315 cm −1 serves as a sensitive, label‐free probe for the local protonation of the amide group.